IMPLEMENTATION OF COGNITIVE BEHAVIORAL THERAPY (CBT) FOR THE ELDERLY IN REDUCING ANXIETY DUE TO LANDSLIDES IN MARGAMUKTI VILLAGE-BANDUNG REGENCY - Tukino Tukino (Politeknik Kesejahteraan Sosial Bandung, 2021)
This study aims to reveal the application of therapeutic communication in reducing anxiety experienced by elderly victims of landslides disaster in Margamukti Village, Pangalengan District, Bandung Regency. Specifically, this is to determine: 1) the physical condition of the elderly victims of landslides, 2) the psychological conditions of the elderly victims of landslides, 3) the social conditions of the elderly victims of landslides, 4) the application of therapeutic communication to reduce anxiety experienced by the elderly after landslides. This study uses a quantitative approach with a single subject design (SSD). The data collection technique is done through questionnaires, interviews, and observations. Analysis of research data using quantitative measurement techniques.The results showed that the application of therapeutic communication to respondent